Penguatan Literasi Digital Generasi Muda melalui Pelatihan Media Digital dan Pembuatan Konten Digital - Sumartias, Suwandi; Suryana, Asep; Ariadne, Evie; Ratnasari, Eny (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
High school students at State Senior High School of Rancaekek are the young generation who have strategic potential in social change. The lack of digital literacy for high school students can be a threat to the ideals of a Golden Indonesia in 2045. For this reason, digital media literacy training and content creators are needed for Rancaekek state high school students, Bandung Regency. This training is carried out directly using interactive lecture methods and focus group discussions (FGD), as well as hands-on practice in processing social media content. The training has succeeded in increasing students' awareness and knowledge about digital media and content creators. Mainly seen from the increase in awareness and knowledge regarding social media content that needs to be studied and filtered before spreading such as hoaxes, fake news, hate speech and so on which is reflected in the results of the pre-test and post-test. The students showed a significant increase in knowledge and skills about the benefits and impacts of digitization, how to avoid hoax news, the Canva application as an application that can support learning and work, and procedures for creating content on social media. Apart from that, in this activity there was also an introduction to CV and LinkedIn as well as the use of Canva and Google Digital Garage. Recommendations for training activities at SMAN Rancaekek are the need for gradual continuation of digital literacy training for students. In addition, school policies are needed to develop digital media literacy agendas as an important part of the teaching and learning process.